Aspects of Weak, s-cs and Almost Injective Rings - Zeyada, Nasr A.; Amin, Amr K. (Sarajevo Journal of Mathematics, 2024)
It is not known whether right CF-rings (FGF-rings) are right artinian (quasi-Frobenius). This paper gives a positive answer of this question in the case of weak CS (s-CS) and GC2 rings. Also we get some new results on almost injective rings.